2017
DOI: 10.2147/ndt.s135190
|View full text |Cite
|
Sign up to set email alerts
|

Novel urinary metabolite signature for diagnosing postpartum depression

Abstract: BackgroundPostpartum depression (PPD) could affect ~10% of women and impair the quality of mother–infant interactions. Currently, there are no objective methods to diagnose PPD. Therefore, this study was conducted to identify potential biomarkers for diagnosing PPD.Materials and methodsMorning urine samples of PPD subjects, postpartum women without depression (PPWD) and healthy controls (HCs) were collected. The gas chromatography-mass spectroscopy (GC-MS)-based urinary metabolomic approach was performed to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
2
14
2
1
Order By: Relevance
“…However, the OPLS-DA model (multivariate analysis) still viewed these metabolites as differential metabolites responsible for the discrimination between the two groups. Previous metabolic studies also reported the similar results [ 27 , 28 ]. This was because the multivariate analysis found the highest discrimination power after adding these metabolites into the discrimination model.…”
Section: Discussionsupporting
confidence: 85%
“…However, the OPLS-DA model (multivariate analysis) still viewed these metabolites as differential metabolites responsible for the discrimination between the two groups. Previous metabolic studies also reported the similar results [ 27 , 28 ]. This was because the multivariate analysis found the highest discrimination power after adding these metabolites into the discrimination model.…”
Section: Discussionsupporting
confidence: 85%
“…Among the four biomarkers identified here, the significantly decreased N -methylnicotinamide and hippuric acid levels, and increased azelaic acid level, were also found in patients with depression alone; 22 , 23 the decreased N -methylnicotinamide level and increased azelaic acid level were also found in patients with BD alone 19 . Meanwhile, Lin et al 56 reported that the levels of N -methylnicotinamide and hippuric acid were also significantly changed in patients with postpartum depression. Hou et al 57 also found the significantly altered N -methylnicotinamide and hippuric acid levels in hepatitis B patients with depression.…”
Section: Discussionmentioning
confidence: 99%
“…The higher abundance of glucose combined with the higher lactate to pyruvate ratio indicate alterations in both the tricarboxylic acid (TCA) and the Cori cycles which have been associated with metabolic stress conditions 46 . Lin et al 20 , reported also significant lactate abundance differences in the urine metabolomic study among postpartum depressed women, compared with both postpartum controls and non-pregnant controls. Plasma arginine, an amino acid, has previously been reported lower among women with antenatal depression in the first trimester, when compared with healthy controls 52 .…”
Section: Discussionmentioning
confidence: 92%
“…Metabolomics has previously been used in psychiatry research to study, e.g., metabolic profile in relation to major depressive disorder and posttraumatic stress disorder [16][17][18][19] , however, among women experiencing depression or depressive symptoms during the peripartum period the literature is scarcer. A study of urine metabolomics in postpartum depression identified a panel of five biomarkers (formate, succinate, 1-methylhistidin, α-glucose, and dimethylamine), which could distinguish postpartum depressed from postpartum non-depressed women, as well as from healthy controls (area under curve (AUC) in training set = 0.948 and in testing set = 0.944) 20 . In addition, a recent metabolomics study identified ten metabolites that had an altered abundance among postpartum depressed women compared with healthy controls 21 .…”
Section: Introductionmentioning
confidence: 99%